Diffusion of coronavirus and awareness among the people of western India: Analyses the role of print media - Pandey, Hemant Kumar; Kumar, Subhash; Dixit, Prabhat (Indian Journal of Community Health, 2022)
Introduction: Media is considered the most powerful platform to create awareness in human society. It plays an important role in spreading public awareness and disseminating information about pandemic diseases such as coronavirus. A survey through a questionnaire was used and the descriptive analysis of questions as asked to the people on COVID 19 published by the leading newspapers of Rajasthan, western India was done to analyze the role print media played in spreading awareness about Coronavirus Disease (COVID-19). Materials and Methods: The objectives used both quantitative and qualitative methodology. In the quantitative method, a self-structured questionnaire was circulated among the various professionals. A descriptive method of secondary sources was also used to measure the effect of articles and advisements on the people published in the newspapers. Results: A total of 106 various professionals participated in the study. The research reveals that 56 percent of males and 43 percent of females are part of this research; more than 80 percent of respondents belong to the age group of fewer than 40 years. Among the active respondents, 91 percent are said to read the newspaper regularly. The study also shows that 96 percent of respondents are read articles, news, columns related to COVID-19 and particular about Coronavirus. Nearly 91 percent of respondents are in favor that media coverage of COVID-19 has improved their knowledge of Coronavirus. Around 93 percent of respondents agree that media spreading awareness among the people on Coronavirus through newspaper published articles, news, and advisements. The study exhibits that 95 percent of respondents expressed their views that print media has played an active role in disseminating the government directives on Coronavirus and almost 97 percent of the respondents are opined that print media will play a more effective role in spreading awareness on coronavirus. Conclusion: The respondents expressed that print media has played a vital role in spreading awareness on the pandemic of coronavirus disease. The newspaper spread awareness among the people on coronavirus through newspaper published articles, news and advisements. The newspaper also published a variety of queries and doubts as asked by the people to Doctors on coronvirus.